THE USE OF GOOGLE TRANSLATE BY STUDENTS IN WRITING A NARRATIVE ESSAY - Nuri Nadifhah Khairunisa; Nunung Fajaryani (JAMBI-ENGLISH LANGUAGE TEACHING, 2022)
Learning English means learning the four skills, namely listening, speaking, reading, and writing. Of the four skills, writing is the most difficult skill to acquire. Fortunately, in this 21st century, technological developments are very helpful for us, especially in language. Many translation tools are very easy to use. One of the translation tools that is available to use by people nowadays is Google Translate. This research focused on the use of Google Translate in the writing narrative essay of 3rd semester English education students at Jambi University and used qualitative approach. The results of this research showed that students use Google Translate to help them solve their problems with vocabulary and grammar. Even though Google Translate could not fully help students to improve their writing skills, it is known to have a contribution to making students more independent, they will work alone, not depending on lecturers and friends. Students used Google Translate to ease their work in writing.